2020
DOI: 10.1016/j.celrep.2019.12.036
|View full text |Cite
|
Sign up to set email alerts
|

FOXD3 Regulates VISTA Expression in Melanoma

Abstract: Highlights d VISTA is heterogeneously expressed on melanoma cells d VISTA expression promotes tumor onset and alters the immune microenvironment d FOXD3 suppresses the expression of VISTA d BRAF/MEK inhibitor treatment reduces levels of VISTA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 55 publications
3
32
0
Order By: Relevance
“…Rosenbaum et al observed that VISTA is expressed in melanoma patient samples and cell lines. Furthermore, tumor cellspecific expression of VISTA, which is regulated by factor forkhead box D3 (FOXD3), promotes tumor onset and enhances PD-L1 expression on tumorinfiltrating macrophages in vivo and is associated with increased intra-tumoral T regulatory cells [19]. There is some evidence that PD-L1/VISTA expression correlates with melanoma survival [19,32,33].…”
Section: Melanomamentioning
confidence: 99%
“…Rosenbaum et al observed that VISTA is expressed in melanoma patient samples and cell lines. Furthermore, tumor cellspecific expression of VISTA, which is regulated by factor forkhead box D3 (FOXD3), promotes tumor onset and enhances PD-L1 expression on tumorinfiltrating macrophages in vivo and is associated with increased intra-tumoral T regulatory cells [19]. There is some evidence that PD-L1/VISTA expression correlates with melanoma survival [19,32,33].…”
Section: Melanomamentioning
confidence: 99%
“…TAMs express high levels of V-domain Ig suppressor of T cell activation (VISTA), another negative immune checkpoint, which is correlated with resistance to immunotherapy [ 154 , 155 ]. VISTA, associated with a significant decrease of survival in primary melanomas, in vivo, promotes a protumoral microenvironment mediated by upregulation of Tregs’ levels and PDL-1 expression on macrophages’ surface [ 155 , 156 , 157 , 158 ].…”
Section: Tme Implications In Drug Resistance For Melanomamentioning
confidence: 99%
“…V-domain Immunoglobulin Suppressor of T cell activation (VISTA; alias PD-1H, Gi24, DD1α, Vsir, or Dies1) is an inhibitory molecule expressed on many cell types including DCs, other myeloid cells, CD4 + and CD8 + T cells as well as tumor cells [ 516 , 517 , 518 ]. VISTA acts as both, receptor and ligand [ 519 ].…”
Section: Dcs Orchestrate T Cell-driven Immunitymentioning
confidence: 99%
“…Further, VISTA was upregulated by p53 activity contributing to the clearance of dead cells by boosting phagocyte functions [ 518 ]. Thus, VISTA might be important on different cell types including apoptotic cells, phagocytes and T cells, to retain unresponsiveness to antigens derived from dead cells and consequently for the immunological silencing [ 517 , 521 ]. However, the very same mechanisms might be hijacked by cancer cells to escape immune surveillance [ 517 , 521 ].…”
Section: Dcs Orchestrate T Cell-driven Immunitymentioning
confidence: 99%
See 1 more Smart Citation